Metagenomic and culture-based genomics reveal virulence and resistance risks in Manila clam microbiomes - Yaling Wang; Linan He; Xing Hu; Yuhan Guan; Xiangnan Chen; Jiahui Du; Jiayan Chen; Chensheng Ma; Lianwei Ye (Food Microbiology, 2026)

DDM1 Controls Heritable Natural Epigenetic Variation in Arabidopsis - Peng Zhang; Datong Xing; Muhammad Shahbaz Chishti; Linan Xie; Qingzhu Zhang (Molecular Ecology, 2025)
As a part of epigenetic modifications, DNA methylation involves the addition of a methyl group to cytosine. In plants, this process occurs in three sequence contexts (CG, CHG and CHH) through two pathways: de novo DNA methylation and DNA methylation maintenance. DNA methylation is highly conserved between ecotypes due to its heritability and role in genomic stability. However, numerous naturally occurring differentially methylated regions (NMRs) exist between ecotypes, which are also heritable and contribute to differential gene expression and phenotypic variation. Decreased DNA methylation observed in mutants of RdDM or DNA methylation maintenance pathways highlights the potential roles of these pathways in NMR formation and inheritance. Nevertheless, the complexity of plant DNA methylation across different contexts and pathways has made the contributions of these two pathways in NMR formation and inheritance remain unclear. To address this, we chose two Arabidopsis thaliana ecotypes, Col‐0 (Col) and C24, and utilised mutants of pol4/5 and ddm1 in both ecotypes. By examining the changes in NMRs within these mutants, we aimed to elucidate the roles of DNA methylation pathways in NMR formation and inheritance. Our results revealed (1) NMRs can be categorised into three types, but classification is not solely based on methylation contexts; (2) compared to RdDM, the DNA methylation maintenance pathway plays a more dominant role in NMR formation and is less influenced by SNPs; (3) DNA methylation maintenance, rather than RdDM, controls NMR inheritance. Our findings highlight the role of the DNA methylation maintenance pathway in NMR formation and inheritance.

The dominant influence of muddy bottom currents on organic-rich fine-grained sedimentary rocks: The lower Congo Basin, west Africa - Bin Zhang; Hongtao Zhu; Xianghua Yang; Zhiwei Zeng; Huang Xing; Linan Pang (Marine and Petroleum Geology, 2024)

CNT-based water-induced generator for effective self-powered devices via superior synergism between electrokinetic and galvanic effects - Linan Xu; Wenxing Wang; Xiaoguang Li; Hongjian Yu; Xinyuan Liu; Yang Zhang; Hongyang Xu; Song Lin; Xing Yi Ling; Haitao Li (Chemical Engineering Journal, 2023)

Design of hybrid La1-Ce CoO3- catalysts for lean methane combustion via creating active Co and Ce species - Lei Jiang; Danyang Li; Guixian Deng; Chunqiang Lu; Linan Huang; Zhiqiang Li; Haiwen Xu; Xing Zhu; Hua Wang; Kongzhai Li (Chemical Engineering Journal, 2023)

Biodegradation of avermectin by Bacteroidetes endosymbiont strain LYH - Zaixing Li; Cunyi Song; Jingliang Yang; Jianbo Guo; Linan Xing (World Journal of Microbiology and Biotechnology, 2008)